Dehumanization of the “Other”: Animal Metaphors of Defeated Enemies in the New Kingdom Military Texts - el Magd, Ahmad Abo.
From the earliest periods, the Egyptians represented foreigners in submissive positions, a propagandist motif reflecting either true Egyptian domination or magic thinking meant to cast its spell on reality. The dominance over foreign enemies was portrayed in a variety of contexts: reliefs on temple walls, statuary, various artifacts, texts, etc., using brutal, aggressive, hostile, and humiliating imagery. This article proposes that the use of animal metaphors supported the stereotypical idea of Egyptian supremacy over their enemies and also played an important role in psychological warfare during the New Kingdom as the traditional enemies of Egypt are depicted as weak, naïve, and easily controlled. Even they are not worthy to live as they represent a threat to MAat. The author follows a three-tiered analysis: zoological identification and literary perception of the animal, the dynamic relation between the specific animal metaphor and its literary adaptation, and finally the application of the (animal) metaphor within its original context, i.e., the recorded texts of specific wars in its historical and strategic context.